Analysis of Buying and Selling Mystery Boxes on the Online Marketplace in the Islamic Law Perspective - Mabruroh, Mabruroh; Sunardi, Dedi; Tarihoran, Naf'an; Sanusi, Ahmad; Usman, Usman (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2023)
Buying and selling is an activity in everyday life and has a long history for humans, it has become a daily social interaction, humans cannot live alone but must help each other in every matter, this also happens in the matter of buying and selling, in Islamic law this is has been regulated as well as the legal process, because this buying and selling activity can also cause doubts or damage to goods where it cannot be ascertained how the quality sold, in the online marketplace there are activities using this scheme, we try to analyze the Islamic religious perspective for this scheme. This research uses a qualitative research approach, which boils down to literature research methods, and collects source sources from Books, E-books, E-journals, Thesis, Qur'an and Hadith. The results of the analysis of this study show that buying and selling (Mystery box) on the online marketplace in the online buying and selling scheme some opinions related to jurisprudence show permissible, but Imam Shafi'i forbids it because it can be called buying and selling with the Gharar method